A National Study to Compare Effective Management of Constipation in Children Receiving Concurrent Versus Standard Hospice Care. Issue 1 (February 2022) - Lindley, Lisa C.; Keim-Malpass, Jessica; Cozad, Melanie J.; Mack, Jennifer W.; Svynarenko, Radion; Fornehed, Mary Lou Clark; Stone, Whitney; Qualls, Kerri; Hinds, Pamela S.
Abstract : Constipation is a distressing and uncomfortable symptom children experience at end of life. There is a gap in knowledge about how different approaches to hospice care delivery might improve pediatric symptom management of constipation. The purpose of this study was to evaluate the effectiveness of pediatric concurrent hospice versus standard hospice care to manage constipation. Medicaid data (2011-2013) were analyzed. Children who were younger than 21 years enrolled in hospice care and had a hospice enrollment between January 1, 2011, and December 31, 2013, were included. Instrumental variable analysis was used to test the effectiveness of concurrent versus standard hospice care. Among the 18 152 children, approximately 14% of participants were diagnosed or treated for constipation from a nonhospice provider during hospice enrollment. A higher proportion of children received nonhospice care for constipation in concurrent hospice care, compared with standard hospice (19.5% vs 13.2%), although this was not significant ( β = .22, P < .05) after adjusting for covariates. The findings demonstrated that concurrent care was no more effective than standard hospice care in managing pediatric constipation. Hospice and nonhospice providers may be doing a sufficient job ordering bowel regimens before constipation becomes a serious problem for children at end of life.